L’évolution de l’inspiration poétique républicaine de Mameli à Carducci : de l’antimonarchisme mazzinien et jacobin à la « démocratie dynastique » - Laura Fournier-Finocchiaro (Laboratoire Italien)
The article examines the evolution of the Republican poetic inspiration in the second half of the nineteenth century. While in 1848-1849, the compositions of the major Republican poets of the Risorgimento (Goffredo Mameli, Francesco Dall’Ongaro, Alessandro Poerio, Luigi Mercantini…) are largely influenced by the teachings of Giuseppe Mazzini, in 1859-1860 the Republican inspiration evolves into Garibaldi’s positions, celebrating national unity under the rule of the House of Savoy, in the name of the primacy of the struggle for independence. After Italian Unity, the poetic of anti-monarchism revolt is carried on by Giosue Carducci, spokesman of the Italian revolutionary movement in the cultural sector with its Jacobin poetry. But the seeking of conciliatory solutions between democratic commitment and respect for the “people” who chose to be represented by the Monarch pushes the poet to deprive himself of the Republican illusion and to celebrate the House of Savoy as best guarantor to defend the supreme value of Unity.